(untitled) (Baghdad Science Journal, 2023)
Infectious diseases pose a global challenge, necessitating an exploration of novel methodologies for diagnostics and treatments. Since the onset of the most recent pandemic, COVID-19, which was initially identified as a worldwide health crisis, numerous countries experienced profound disruptions in their healthcare systems. To combat the spread of the COVID-19 pandemic, governments across the globe have mobilized significant efforts and resources to develop treatments and vaccines. Researchers have put forth a multitude of approaches for COVID-19 detection, treatment protocols, and vaccine development, including groundbreaking mRNA technology, among others. This matter represents not only a scientific endeavor but also an essential addition to our arsenal for combating infectious diseases. This concern is underscored by the inclusion of eleven articles in this issue, each highlighting the urgent need to boost global resources for investigating, detecting, treating, and responding to emerging infections. Furthermore, there is a pressing call for the effective coordination and guidance of Arabian research initiatives, in conjunction with the efforts of Afro-Asian countries, to collectively address the challenges at hand and enhance overall outcomes. This special issue of Baghdad Science Journal on COVID-19 and anti-infective strategies provides an overview of infectious disease and anti-infective strategies management for detection, treatment protocol, and vaccine development including mRNA with many other strategies, by publishing articles on recent research concepts.